The Role of Mediation in Alternative Dispute Resolution as an Effective Solution for Non-Litigation Dispute Resolution - Abdul Hannan (Penerbit Hellow Pustaka, 2025)
Alternative Dispute Resolution (ADR) is a dispute resolution approach that prioritizes solutions outside of litigation, with the aim of creating a faster, cheaper, and more efficient process. One of the main methods in ADR is mediation, which offers a participatory and collaborative approach between the disputing parties. This article examines the role of mediation in ADR as an effective solution for non-litigation dispute resolution, focusing on the working mechanism, advantages, and challenges faced. This study uses a qualitative approach with literature review and case analysis methods to describe the effectiveness of mediation in various types of disputes, including business, family, and environmental disputes. The results of the study indicate that mediation has great potential in creating win-win solutions without the need for a complicated court process. The success of mediation is greatly influenced by the neutrality of the mediator, openness of communication, and the commitment of the parties to resolve the dispute peacefully. This article also highlights the challenges in implementing mediation, such as the lack of public understanding of ADR and the limited number of professional mediators. Recommendations are given to improve the role of mediation through strengthening regulations, mediator training, and public awareness campaigns. Thus, mediation can be an effective and sustainable alternative in resolving disputes in the modern era.